2000
DOI: 10.1046/j.1432-1327.2000.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic differences between porcine blastocyst and placental aromatase isozymes

Abstract: Two isozymes of porcine aromatase, the placental and the blastocyst forms, were expressed in CHO cells using the mammalian cell transfection method. Using an`in-cell' assay (a 3 H-water release method), catalytic parameters of the porcine placental aromatase were found to be very similar to those of the human enzyme; however, the activity of the blastocyst isozyme was found to be one-thirtieth that of the placental isozyme. Product isolation assay (using testosterone as the substrate) revealed that the major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…The pig (Sus scrofa) expresses three distinct isozymes of the aromatase protein that are specific for the gonads, placenta, and embryo [26]. Although aromatase isozymes in pigs share Ͼ90% amino acid sequence identity, they exhibit distinct catalytic properties and responses to different aromatase inhibitors [27]. To our knowledge, the possibility that sheep express isozymes of aromatase has never been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The pig (Sus scrofa) expresses three distinct isozymes of the aromatase protein that are specific for the gonads, placenta, and embryo [26]. Although aromatase isozymes in pigs share Ͼ90% amino acid sequence identity, they exhibit distinct catalytic properties and responses to different aromatase inhibitors [27]. To our knowledge, the possibility that sheep express isozymes of aromatase has never been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Sulphoconjugation may serve to regulate the biological availability of 19-norA for whatever role the 'free' steroid might play. It has been reported that 19-norA inhibited the conversion of androgen to estrogen by aromatase, perhaps by competing for binding to the active site of the enzyme [22]. The well known anabolic action of norandrogens also has to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…No difference seems to exist for the localization of aromatase protein and transcript for the early equine embryo when compared to the porcine embryo, despite the transient nature of the enzyme activity in the latter [28]. Special interest lies in the report that the major product of the blastocyst form in the pig was the 19-norandrogen when transfected CHO cells were incubated with [4-14 C]-testosterone [22]. Our finding of high concentrations of 19-norA in y-s fluid of the mare gives support to these in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations